Composite magnetoelectrics : materials, structures, and applications - Srinivasan, G.; Priya, Shashank; Sun, Nian X. (Woodhead Publishing, 2015)
Annotation "Composite Magnetoelectrics: Materials, Structures, and Applications" gives the reader a summary of the theory behind magnetoelectric phenomena, later introducing magnetoelectric materials and structures and the techniques used to fabricate and characterize them. Part two of the book looks at magnetoelectric devices. Applications include magnetic and current sensors, transducers for energy harvesting, microwave and millimeter wave devices, miniature antennas and medical imaging. The final chapter discusses progress towards magnetoelectric memory. Summarises clearly the theory behind magnetoelectric phenomenaStrong coverage of fabrication and characterisation techniquesReviews a broad range of current and potential magnetoelectric devices.
Keywords: Composite materials -- Magnetic properties.; Composite materials -- Electric properties.; elektronické knihy; electronic books